Why do animals sleep through winter? - Arvetis, Chris; Palmer, Carole; Buckley, James, 1933- ([Chicago] : Childrens Press, 1987)
Animal characters, simple words, and colorful pictures explain why animals sleep through the winter.
3.0
K-3
Keywords: Hibernation -- Juvenile literature; Hibernation; Animals -- Hibernation